'Irresponsible and a Disservice': The integrity of social psychology turns on the free will dilemma. (10th November 2011) - Miles, James B.
<x xml:space="preserve">Abstract</x> Over the last few years, a number of works have been published asserting both the putative prosocial benefits of belief in free will and the possible dangers of disclosing doubts about the existence of free will. Although concerns have been raised over the disservice of keeping such doubts from the public, this does not highlight the full danger that is presented by social psychology's newly found interest in the 'hard problem' of human free will. Almost all of the work on free will published to date by social psychologists appears methodologically flawed, misrepresents the state of academic knowledge, and risks linking social psychology with the irrational.